PERAN DIGITAL MARKETING DALAM MENINGKATKAN DAYA SAING UMKM KULINER KOTA MOJOKERTO - Rachmawati, Farikha; Finaliyani Putri , Dhelittya (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
The development of digital technology has significantly transformed marketing patterns and consumer behavior, including within the micro, small, and medium enterprises (MSME) sector. In Mojokerto City, culinary MSME players are required to adapt to these changes to remain competitive and expand their market reach. This study aims to analyze the role of Digital Marketing in strengthening the competitiveness of culinary MSMEs and to identify effective Digital Marketing strategies applied in the field. This research employs a qualitative approach through field observations, in-depth interviews, and documentation of MSME actors who utilize digital platforms such as social media, marketplaces, business websites, and online food delivery services. The findings reveal that Digital Marketing contributes to increased sales, market expansion, stronger brand positioning, and improved customer loyalty through more interactive communication channels. In addition, business owners can utilize digital data to analyze consumption trends and formulate more targeted marketing strategies. However, challenges remain in the form of limited technological literacy and inconsistent management of digital content. Therefore, continuous training and mentoring are required to optimize the implementation of Digital Marketing in a comprehensive and sustainable manner. Keywords: MSMEs in Mojokerto City, Digital Marketing, Competitiveness, Social Media